Quantitative comparison of protein-protein interaction interface using physicochemical feature-based descriptors of surface patches - Shin, Woong-Hee; Kumazawa, Keiko; Imai, Kenichiro; Hirokawa, Takatsugu; Kihara, Daisuke (Frontiers in Molecular Biosciences, 2023)
Driving mechanisms of many biological functions in a cell include physical interactions of proteins. As protein-protein interactions (PPIs) are also important in disease development, PPIs are highlighted in the pharmaceutical industry as possible therapeutic targets in recent years. To understand the variety of PPIs in a proteome, it is essential to establish a method that can identify similarity and dissimilarity between PPIs for inferring the binding of similar molecules, including drugs and other proteins. In this study, we developed a novel method, PPI-Surfer, which compares and quantifies similarity of local surface regions of PPIs. PPI-Surfer represents a PPI surface with overlapping surface patches, each of which is described with a three-dimensional Zernike descriptor (3DZD), a compact mathematical representation of 3D function. 3DZD captures both the 3D shape and physicochemical properties of the protein surface. The performance of PPI-Surfer was benchmarked on datasets of PPIs, where we were able to show that PPI-Surfer finds similar potential drug binding regions that do not share sequence and structure similarity. PPI-Surfer is available at https://kiharalab.org/ppi-surfer.